CUSTOMER LOYALTY: THE INFLUENCE OF PRICES AND PROMOTIONS ON CUSTOMER LOYALTY : CASE STUDY AT MINIMARKET IN BANDUNG - Putra, Wahyu Pramana Arya; Fransiska, Friza Viola; Lilyana, Fitria; Hersusetiyati, Hersusetiyati; Lusiana, Senny (Multifinance, 2025)
Indomaret customers in Bandung tend to compare prices at one minimarket with another, especially if the minimarkets are located close to each other. The price of goods in minimarkets is a fixed price that cannot be negotiated by customers. Customers tend to see product promotions in the form of discounts or price discounts, as well as other promotions such as bundling packages, when they want to make a purchase. This research was conducted to describe and analyze prices, promotions, and customer loyalty, as well as to measure the influence of prices and promotions on customer loyalty at Indomaret in Bandung. The method used in this research is descriptive and a verification analysis method. The population in this research is the Indomaret in Bandung customers. The analytical method used in this research is multiple linear regression analysis. Based on partial research results, prices have a positive and significant effect on customer loyalty, and promotions have a positive and significant effect on customer loyalty. Simultaneously, price and promotion have a positive and significant effect on Indomaret customer loyalty in Bandung.